Simultaneous Determination and Pharmacokinetic Study of Metformin and Rosiglitazone in Human Plasma by HPLC-ESI-MS - Chen, Lingyun; Zhou, Zhifeng; Shen, Mei; Ma, Ande (Journal of chromatographic science, 2011)
A fast, sensitive and specific high-performance liquid chromatography tandem mass spectrometry method was develope for simultaneous determination of metformin and rosiglitazone in human plasma. With phenformin as an internal standard, the analysis was carried out on a C18 column (50 mm × 2.1 mm, 3.5 µm) using a mobile phase consisting of acetonitrile-10 mM ammonium acetate (20:80, v/v). The detection was performed by tandem mass spectrometry via electrospray ionization. Linear calibration curves were obtained in the concentration of 1.054-263.5 ng/mL for rosiglitazone and 4.040-5050 ng/mL for metformin. The method was applicable to clinical pharmacokineti study of metformin and rosiglitazone in healthy volunteers following oral administration.